Determinants of Audit Report Lag in Indonesia - Audika, Brian; Priono, Hero; Sari, Rida Perwita (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
Financial statements are a very important part of the company, especially for public companies. Users of financial statements are very broad, ranging from internal managerial as performance measurement and decision making to investors and creditors. The purpose of this study was to determine and analyze empirically the effect between audit committee size, independent audit committee, audit committee expertise, and diligent audit committee with audit report lag. This type of research is quantitative research. The data analysis method in this study uses the Smart Equation Model Partial Least Square (SEM-PLS). The variables that will be observed in this study are audit committee size, audit committee independence, audit committee expertise and audit committee diligence as independent variables, while audit report lag is the dependent variable. Company size, profitability, KAP reputation are used as control variables in 78 property sector companies listed on the Indonesia Stock Exchange in 2021-2022. The results of this study provide empirical evidence that good GCG implementation can have an impact on audit report lag.